WEB-BASED MANAGEMENT INFORMATION SYSTEM WITH CODEIGNITER FRAMEWORK - Nst, Fifi Anggiani Br; Lubis , Arif Ridho; Sembiring, Boni Oktaviani (Pena Cendekia Insani, 2022)
The need for shelter becomes very needed at this time, especially people from outside the city who want to work or continue their education to other cities. So that the need for boarding houses to increase and demand by many people. The system that is running on the full boarding house is still done manually where, there is no system that can help in managing his boarding house, where people who want boarding must come directly to see the facilities they have, room status and costs. And there is no system that can help the owner in managing boarding house payments. The development of this system uses the waterfall method. Web-based full boarding management information system can manage boarding payment data and tenant data management.